2020
DOI: 10.1016/s2589-7500(20)30017-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel digital intervention for actively reducing severity of paediatric ADHD (STARS-ADHD): a randomised controlled trial

Abstract: Background Attention-deficit hyperactivity disorder (ADHD) is a common paediatric neurodevelopmental disorder with substantial effect on families and society. Alternatives to traditional care, including novel digital therapeutics, have shown promise to remediate cognitive deficits associated with this disorder and may address barriers to standard therapies, such as pharmacological interventions and behavioural therapy. AKL-T01 is an investigational digital therapeutic designed to target attention and cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
238
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(254 citation statements)
references
References 31 publications
12
238
1
3
Order By: Relevance
“…Furthermore, we would like to discuss potential implications of our results at the intersection of computer sciences, health care and the gaming industry. Considering that there are already customized video games that are used for clinical purposes (Kollins et al, 2020); and video games where on-screen characters may even be controlled by means of brain oscillatory activity or event-related potentials using brain-computer interfaces (Bayliss, 2003;Nijholt et al, 2009), which may enable people with a physical disability to enjoy video gaming and feel more inclusive (see, Bos et al, 2010, for a more detailed review), one might question the significance of gaming effects associated with commercially available video games. One of the largest shortcomings of the latter is the lack of standardization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we would like to discuss potential implications of our results at the intersection of computer sciences, health care and the gaming industry. Considering that there are already customized video games that are used for clinical purposes (Kollins et al, 2020); and video games where on-screen characters may even be controlled by means of brain oscillatory activity or event-related potentials using brain-computer interfaces (Bayliss, 2003;Nijholt et al, 2009), which may enable people with a physical disability to enjoy video gaming and feel more inclusive (see, Bos et al, 2010, for a more detailed review), one might question the significance of gaming effects associated with commercially available video games. One of the largest shortcomings of the latter is the lack of standardization.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, video gaming might represent a promising tool both for investigating human learning and therapeutic use in clinical populations (e.g., in patients with amblyopia, see Gambacorta et al, 2018). In this sense, for instance, EndeavorRx TM (Akili Interactive Labs, Boston, MA, United States), a racing video game customized to treat children with ADHD (Kollins et al, 2020), was approved by the Food and Drug Administration (FDA), recently.…”
Section: Introductionmentioning
confidence: 99%
“…Thus moving away from training multiple specific mechanisms (whether auditory or cognitive) and towards the broader and potentially more motivating training offered by action video game play e.g. 31 . The participants were grouped by pre-existing gaming experience and received no study-related training.…”
mentioning
confidence: 99%
“…Kollins et al [ 42 ▪ ] reported their large randomized, double blind, parallel-group, controlled trial involving 346 children aged 8–12 years. The intervention programme was a home-based digital game with cognitive training components involving attention control and set shifting, within built real-time adaptive mechanism to personalize the training level.…”
Section: Resultsmentioning
confidence: 99%